??- Statistical convergence of order ? on time scales - Er, Busra Nur; Altin, Yavuz (Univ Craiova, 2022)
In this study, we introduce the notions Delta lambda-statistical convergence of order alpha (for alpha is an element of (0, 1]) and lambda p- summability of order alpha (for alpha is an element of (0, 1]) on an arbitrary time scale. Moreover, some relations about these notions are obtained. We define Delta lambda-statistical bound-edness of order alpha (for alpha is an element of (0, 1]) on a time scale. Furthermore, we give connections between S(lambda,alpha) T (b) , S(beta,theta) T (b) and ST (b) for various sequences mu Delta lambda(t) and mu Delta beta (t) which are determined in class ?. 2010 Mathematics Subject Classification. 40A05, 46A45, 26E70.
Keywords: Key words and phrases; Statistical convergence; statistical boundedness; sequence spaces; time scales